ANALISIS ASPEK PENGAWASAN, REWARD DAN PUNISHMENT TERHADAP KEPATUHAN PENGGUNAAN APD PADA PEKERJA KETINGGIAN PROYEK PT X TAHUN 2023 - Winda Nadya (2024)
The PT X project is a construction project that involves work at height and there were 14 cases of minor work accidents, such as punctured, scratched, and pinched. As well as the finding of dangerous behavior in height workers, namely not using full body harness. This study aimed to analyze the aspects of supervision, reward, and punishment on compliance with the use of PPE of working at heights. This study used quantitative methods cross-sectional study design. The total sample used was 52 respondents by total sampling selection. Data collection methods with observation and questionnaires. Data analysis used univariate, bivariate with chi-square test, and multivariate with multiple logistic regression test. The results of the bivariate analysis showed that there was a relationship between knowledge (p-value 0.005), attitude (p-value 0.011), supervision (p-value 0.014), and punishment (p-value 0.011) with worker compliance of PPE. While the reward variable (p-value 0.491) has no relationship with worker compliance of PPE. The results of multivariate analysis showed knowledge to be the most dominant variable on worker compliance of PPE (POR: 7.441; 95% CI: 1.351 - 40.981). The company could hold training programs or training related to the importance of using PPE on working at height so that workers' knowledge increases.